2017
DOI: 10.5539/sar.v7n1p92
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Release of Soil Nitrate and Labile C in A Legume-Maize Rotation in Zimbabwe

Abstract: This study compared the effect of a weedy fallow (5.2 t/ha biomass), a velvet bean (Mucuna pruriens) cut for hay (7.2 t/ha biomass) and a green-manured M. pruriens (6.49 t/ha biomass) on the dynamics of soil N and C in a maize crop. An on-farm, farmer participatory experiment was established on a farmer's field in Wedza District, Zimbabwe. Soil mineral N and labile carbon were determined at intervals upto 120 cm depth, at maize planting and at 1 and 2 weeks after planting. Before planting, the soil mineral N c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Considering the low nutrient holding capacity of the loamy sand soil used in our study, a large portion of N mineralized from leguminous residues was probably leached before soil samples were collected at the end of each growing season. This explanation is supported by previous research in Zimbabwe that showed soil nitrate concentrations from 0 to 1.2 m depth declined by 77% from the beginning of the rainy season to 1 week after planting maize (a 6-week span) in fields planted to vining mucuna the previous growing season (Jiri and Mafongoya, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Considering the low nutrient holding capacity of the loamy sand soil used in our study, a large portion of N mineralized from leguminous residues was probably leached before soil samples were collected at the end of each growing season. This explanation is supported by previous research in Zimbabwe that showed soil nitrate concentrations from 0 to 1.2 m depth declined by 77% from the beginning of the rainy season to 1 week after planting maize (a 6-week span) in fields planted to vining mucuna the previous growing season (Jiri and Mafongoya, 2018).…”
Section: Discussionsupporting
confidence: 79%